Structural composite materials - Campbell, F. C. (ASM International, 2010)
This book deals with all aspects of advanced composite materials; what they are, where they are used, how they are made, their properties, how they are designed and analyzed, and how they perform in-service. It covers both continuous and discontinuous fiber composites fabricated from polymer, metal, and ceramic matrices, with an emphasis on continuous fiber polymer matrix composites.
Keywords: Composite materials.; elektronické knihy; electronic books